Implementation Segmentation of Color Image with Detection of Color to Detect Object - Fajar Mahardika; Dhanar Intan Surya Saputra (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Detection of objects in an image 2 dimensional is a process which is quite complex to do. Object detection required a computer vision approach to the desired part of the object can be recognizable computer accurately. The method in this research using waterfall method. This research will describe the application of color segmentation method with the color detection of a digital image to produce image segment object in the form of blob so that the computer can be detected. The object detection process will process the resulting color segment by the process of segmentation so that can know the number of detected objects, the area and the center of the object. This application can take pictures with laptop or notebook webcam. The result of color segmentation based on color detection is strongly influenced by color samples and color tolerance values to which the segmentation process is based. Lighting, location, texture, and contour of objects or background image will greatly affect the results of segmentation and object detection.